PENGARUH WHISTLEBLOWING, AKUNTANSI FORENSIK DAN AUDIT INVESTIGASI DALAM MENDETEKSI FRAUD (STUDI PADA PERWAKILAN BPKP PROVINSI RIAU - SUKMA SOPIYAN ARDIANSYAH (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2023)
This study aims to examine the effect of whistleblowing, forensic accounting and investigative audits in detecting fraud. This type of research is research with a quantitative approach. The population in this study, namely the investigative auditors of the Financial and Development Supervisory Agency (BPKP) Representatives of Riau Province, amounted to 30 auditors. The sampling technique in this study used a saturated sampling technique. The sample in this study was an investigative auditor who worked at the Representative of the Financial and Development Supervisory Agency (BPKP) of Riau Province, which amounted to 30 auditors. The data used in the study is primary data collected by distributing questionnaires directly. Data analysis used multiple linear regression analysis. The results show that whistleblowing has an effect on fraud detection, forensic accounting has no effect on fraud detection, and investigative audits have an effect on fraud detection